A feasible approach for azo-dye methyl orange degradation in siderite/H2O2 assisted by persulfate: Optimization using response surface methodology and pathway. (15th April 2022) - Song, Wei; Li, Ji; Zhang, Xiaolei; Feng, Jianpei; Du, Xing; Wang, Qiao; Fu, Caixia; Qiu, Wenhui; Wang, Zhihong; Gao, Xinlei
Abstract: Siderite was applied to the binary oxidant system of siderite-catalyzed hydrogen peroxide (H2 O2 ) and enhanced with persulfate (PS). In the absence of PS, methyl orange (MO) almost could not be degraded by the siderite/H2 O2 process. However, adding PS significantly improved the capacity of MO to oxidize azo-dye. The influence of individual and interaction of reaction factors have been explored with a simple response surface methodology (RSM) based on central composite design (CCD). The quadratic model with low probabilities (<0.0001) at a confidence level of 95% was satisfactory to predict MO degradation in siderite/H2 O2 /PS system, whose correlation coefficients of R 2 and R 2 -adj were 0.9569 and 0.9264, respectively. Moreover, the optimum operation conditions of 21.20 mM, 2.75 g/L, 3.86 mM, and 4.69 for H2 O2, siderite, PS and initial pH, respectively with the response of C/C0 around 0.047. Radical scavenging experiments and electron spin resonance (ESR) determined that · OH was crucial for MO degradation, while the contribution of SO4 ·- was minor. The surface morphology and iron content of siderite before and after the oxidation process showed clear differences. Possible intermediates and a degradation pathway were proposed based on the results of UV–Vis spectral and GC-MS analysis. Moreover, the toxicity to Vibrio fischeri bioluminescent bacterium has increased in the earlier degradation stage due to the generated by-products and weaken with the continuous treatment. This study demonstrated that the siderite/H2 O2 /PS system was effective over a relatively wide pH range without producing secondary pollutants, making it a promising technology and potential environmentally benign approach to azo-dye wastewater treatment. Graphical abstract: Image 1 Highlights: Adding PS to siderite/H2 O2 system makes it feasible for azo dye degradation. The response surface model well fitted with the actual data and R 2 was 0.9569. · OH and SO4 · - were involved in siderite/H2 O2 /PS system. MO degradation mechanism had been proposed through UV–Vis and GC-MS.